Influence of tilt angle on eddy current displacement measurement. Issue 4 (1st October 2016) - Li, Yang; Sheng, Xianjun; Lian, Meng; Wang, Yongqing
Abstract : For displacement measurement, to explore the influence of tilt angle on sensor's measured values, the relationship between coil equivalent inductance and lift-off under different tilt angles and the relationship between coil equivalent inductance and tilt angle under different lift-offs were investigated by the finite element method in this article, respectively. Comparing the two variation laws, the increase of tilt angle will lead to smaller sensor's measured values. Moreover, the applicability of the transformer-equivalent circuit model has nothing to do with the tilt angle. Besides, the experiments also testify that the measuring errors can be compensated well by the Gaussian function.